Response in Patients With Persistent Pelvic Pain to Motor Imagery Through Auditory or Visual Input—A Pilot Randomized Trial - Borja Perez-Dominguez; Alba Arce-Elorza; Isabel Rubio-Garcia; Esther Diaz-Mohedo (Pain Research and Management)
Trial Registration: ClinicalTrials.gov identifier: NCT06343649